PERAN PERMAINAN LOMPAT TALI DALAM MENGEMBANGKAN MOTORIK KASAR ANAK DI PANTI ASUHAN LKSA JIREH SEMENIFESTARA KOTA MEDAN - Heka Maya Sari Br Sembiring; Joen Parningotan Purba; Floranta Br Tobing; Erna Sintya; Meiberina Br Sitepu (PUAN INDONESIA, 2026)
Limited play spaces and low levels of physical activity among children in urban areas can negatively affect the development of gross motor skills. This community service activity aimed to enhance children’s gross motor development through the implementation of the traditional jump rope game at LKSA Jireh Semeinifestara Orphanage, Medan City. The participants were elementary school–aged children living in the orphanage. The methods used in this activity included initial observation, socialization of the jump rope game, direct practice with supervision, and evaluation through observation of children’s gross motor abilities. The results showed that the jump rope game was able to improve children’s gross motor skills, particularly in terms of balance, movement coordination, and leg muscle strength. In addition, the children demonstrated high enthusiasm and active participation throughout the activity. Therefore, the jump rope game can be considered an effective, simple, and easily implemented physical activity to support gross motor development among children in urban orphanage settings.